PENERAPAN NILAI-NILAI PANCASILA DALAM ORGANISASI DAN PERILAKU BUDAYA GERAKAN PEMUDA ANSOR - AHMAD MUDHOFIR (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
This study aims to describe the application of Pancasila values ??in the organization and cultural behavior of the Ansor Youth Movement. This type of research is a qualitative descriptive research. The subjects taken were 4 respondents from the Grobogan sub-district Ansor administrators. Data collection is done by observation and interviews. The data analysis technique was carried out in 3 stages, namely data reduction, data presentation and drawing conclusions. The technique of checking the validity of the data is using source triangulation. Based on the results of GPA data analysis, Grobogan District always tries to solidify ideology, develop vision, mission, perception, interpretation, and organizational orientation for each cadre. With this, it is hoped that cadres will be formed who are highly dedicated, proactive, critical, humanist, professional, and innovative in order to encourage and bring about change as an answer to the problems faced by this nation. For this reason, realizing the Ansor GP is an unavoidable necessity, and the regeneration process for it is a non-negotiable demand. ABSTRAKPenelitian ini bertujuan mendeskripsikan penerapan nilai-nilai pancasila dalam organisasi dan perilaku budaya gerakan pemuda ansor. Jenis penelitian ini merupakan penelitian deskriptif kualitatif. Subjek yang diambil yakni 4 responden pengurus ansor kecamatan grobogan. Pengumpulan data yang dilakukan yakni observasi dan wawancara. Teknik analisis data dilakukan dengan 3 tahapan yaitu reduksi data, penyajian data dan penarikan kesimpulan. Teknik pemeriksaan keabsahan data yakni menggunakan triangulasi sumber. Berdasarkan hasil analisis data GPA Kecamatan Grobogan senantiasa berusaha memantapkan ideologi, mengembangkan visi, misi, persepsi, interprestasi, dan orientasi organisasi kepada setiap kadernya. Dengan ini diharapkan akan terbentuk kader-kader yang berdedikasi tinggi, proaktif, kritis, humanis, professional, serta inovatif guna mendorong dan mewujutkan perubahan sebagai jawaban atas problematika yang dihadapi bangsa ini. Untuk itu, mewujutkan GP Ansor menjadi kebutuhan tak terelakan, dan proses regenerasi atasnya menjadi tuntutan yang tidak bisa ditawar.